FIRST REPORT OF DESERTOBIA ANKERARIA (STAUDINGER, 1861) (LEPIDOPTERA: GEOMETRIDAE) IN SERBIA (Acta Entomologica Serbica, 2016)
Desertobia ankeraria (Staudinger, 1861) is a Natura 2000 target species and it is included in Anex II of EEC 92/43 Habitat Directive. It is strictly protected species in Slovenia, Croatia and Hungary.It is recorded for the first time in Serbia in Pčinja river valley near Trgovište at locality Vražji Kamen. The species was attracted to the light trap on March 15th, 2016. D. ankeraria usually inhabits inhabits xerothermic oak woodlands and caterpillars are feeding on leaves of Downy Oak Quercus pubescens Wild. and Sessile Oak Q. petraea (Matt.) Liebl. Such habitat and Downy Oak were found at Vražji Kamen during our previous research in southern Serbia.